PENGARUH MODEL RECIPROCAL TEACHING DAN KECERDASAN INTRAPERSONAL TERHADAP HASIL BELAJAR IPS SISWA - Yusrizal Yusrizal; Fatmawati Fatmawati (JURNAL TEMATIK, 2020)
This study aims to: (1) Know the differences in social studies learning outcomes of studentstaught by the reciprocal teaching model compared to conventional models; (2) Knowing the differencein social studies learning outcomes of students who have high interpersonal intelligence compared tolow interpersonal intelligence; (3) Knowing the interaction between learning models and interpersonalintelligence in influencing students' social studies learning outcomes. This research was conducted atPanton Luas Baru Elementary School, Samadua District, South Aceh Regency. The sample in this studywere 27 students in grade V / a and 27 students in grade V / a. Data collection tools using questionnairesand social studies learning test results. Hypothesis testing is done by the Two Way Anova test. Theresults showed that: (1) Social studies learning outcomes of students taught by the reciprocal teachingmodel were higher than those of the conventional model (Fcount = 21,164; sig. 0,000); (2) Social studieslearning outcomes of students who have high interpersonal intelligence are higher than students whohave low interpersonal intelligence (Fcount = 6.756; sig. 0.012); (3) There is an interaction betweenlearning models and interpersonal intelligence in influencing students' social studies learning outcomes(Fcount = 7.054; sig. 0.011)